Sauces: An undiscovered healthy complement in Mexican cuisine - Cárdenas-Castro, Alicia Paulina (2019)
Gastronomic differences between the countries cuisines around the world were largely defined due to the diversification of the use of spices and condiments during the European colonization of America, Asia and Africa. Hence, gastronomy tells the story of thousands of generations in a country and contains the culture of the population in multiple combinations of vegetables, types of meats or spices that depends on the geographical conditions. Particularly, the Mexican diet has been studied in a limited way but the findings of its consumption could ameliorate health status. Pre-Hispanic cultures developed many different dishes that still consumed nowadays. Surprisingly, Mexican population is developing acculturation, which includes lower intake of their most healthy traditional food, and so on, one of them are Mexican sauces, a mixture with hot pepper, tomato, husk tomato, onion, garlic, coriander and salt. It should be noted that the most common ingredients of Mexican sauces have been studied isolated but not combined, as they are frequently consumed. In addition, the potential health effects of the bioactive compounds (BC) that could be found in this staple Mexican food still undiscovered. In this review, the main BC present in common Mexican sauces ingredients and the effects of processing in the content of these compounds are stated in this review.